Antimigraine activity of Ficus deltoidea jack aqueous extract in mice and its possible mechanisms - Salihan, Safuraa (2020)
Migraine is a disabling headache disorder characterized by throbbing headache and associated with various symptoms namely nausea, vomiting and heightened sensitivity to touch and smell. Ficus deltoidea is an herbaceous plant used traditionally in treating pain and headache. As phytomedicine produce alternative therapeutic strategies for migraine pain, the aim of this study is to evaluate the antimigraine properties of Ficus deltoidea (var Trengganuensis) aqueous extract (FDA) and its possible mechanisms. In nonspecific antimigraine study, using animal model of nociception, administration of FDA produced significant antinociceptive effect in acetic acid-induced abdominal writhing test, early and late phase of formalin test and in the hot plate test. In specific antimigraine study, nitroglycerin (NTG)-induced migraine model was used. It is the most studied and well accepted model in antimigraine drug testing. Preliminary tests were done verifying and optimizing the use of this model. The effect of FDA was tested in NTG-induced hyperalgesia using formalin and hot plate test. It was found that FDA produced significant inhibition in both early and late phase of formalin test and significant increase in respond latency in hot plate test. In addition, treatment with FDA significantly reduced the NTG-induced c-fos expression in trigeminal nucleus caudalis (TNC), a relay center in migraine. This study also explored the mechanism of FDA through peripheral and central sensitization, and involvement of serotonergic and dopaminergic pathways. The involvement of FDA in peripheral sensitization was done using kainic acid-induced hyperalgesia in hot plate test, showing significant increase in response latency in group receiving FDA compared to control. In study of central sensitization, using NTG-induced mechanical allodynia in von Frey test, FDA group produced significant improvement in paw withdrawal threshold compared to control. Studies on serotonergic and dopaminergic systems involvement was done by studying the effect of FDA on 5-hydroxytryptophan(l-5-HTP)-induced serotonin syndrome and apomorphine-induced climbing behavior. Results showed FDA significantly inhibited l-5-HTP-induced serotonin syndrome and apomorphine-induced climbing activity. In addition, FDA significantly inhibited NTG induced plasma CGRP using ELISA. These findings suggested that FDA possessed antimigraine activity through inhibition of peripheral and central sensitization with possibility of involvement of dopaminergic and serotonergic mechanism and CGRP inhibition.